Prevalence and risk factors of sepsis-induced cardiomyopathy: A retrospective cohort study. Issue 39 (September 2016) - Sato, Ryota; Kuriyama, Akira; Takada, Tadaaki; Nasu, Michitaka; Luthe, Sarah Kyuragi
Abstract : Abstract: The aim of the study is to evaluate the epidemiology and clinical features of sepsis-induced cardiomyopathy (SICM). A retrospective cohort study was conducted. A total of 210 adult patients with sepsis or septic shock admitted to a Japanese tertiary care hospital from January 1, 2013, to December 31, 2015, who underwent transthoracic echocardiography (TTE) on admission. The definition of SICM was ejection fraction (EF) < 50% and a ≥10% decrease compared to the baseline EF which recovered within 2 weeks, in sepsis or septic shock patients. Our primary outcome was the incidence rate of SICM. Our secondary outcomes were the in-hospital mortality rate and length of intensive care unit (ICU) stay according to the presence or absence of SICM. In total, 29 patients (13.8%) were diagnosed with SICM. The prevalence rate of SICM was significantly higher in male than in female ( P = 0.02). Multivariate logistic regression analyses revealed that the incidence of SICM was associated with younger age (odds ratio [OR], 0.97; 95% confidence interval [CI], 0.95–0.99), higher lactate level on admission (OR, 1.18; 95% CI, 1.05–1.32) and history of heart failure (HF) (OR, 3.77; 95% CI, 1.37–10.40). There were no significant differences in the in-hospital and 30-day mortality between patients with and without SICM (24.1% vs 12.7%, P = 0.15; 20.7% vs 12.1%, P = 0.23). Lengths of hospital and ICU stay were significantly longer in patients with SICM than in those without SICM (median, 43 vs 26 days, P = 0.04; 9 vs 5 days, P  < 0.01). SICM developed in 13.8% of patients with sepsis and septic shock. A younger age, higher lactate levels on admission and history of HF were risk factors.